Наказания / казни за преступления времен Древнего Рима - Toma, Marianna (Chişinău: CEP USM, 2021)
The laws of the XII tables, in fact, became the basis of the criminal law of ancient Rome. During the tsarist period, punishment for crimes was imposed by priests and magistrates. The main powers were possessed only by the king, who presided over the court of “two people” from among the senators. In the republican period, the kings were replaced by consuls. This court considered cases of “encroachment on the sacred interests of the Roman people.” There was still no precise definition of the concept of crime. It was considered only a deliberate act. Among the punishments for crimes, they preferred mainly fines and, of course, the death penalty. It is written in the Laws (Table IX) that only centurial popular assemblies (comitia) had the right to pass death sentences to Roman citizens. It was usually forbidden to take life without trial (but anyone could kill a night thief or a thief captured with a weapon in his hands at the scene of a crime). At the same time, none of the citizens could demand for themselves a deviation from the law, benefits or privileges.
Keywords: Ancient Rom; Tables of laws; Crimes; Executions; Punishments; Death sentences; Punishments for crimes of a religious nature; Judicial arbitrariness